Analisis SWOT sebagai Strategi Pengembangan Kampung Kauman sebagai Kampung Wisata - Salsabilla, Fadira; Nurjayanti, Widyastuti (Prosiding (SIAR) Seminar Ilmiah Arsitektur, 2023)
This study focus on offering development strategies of Kampung Kauman as a tourist village. The object was chosen because it is considered as a tourist area that can be developed because its unique and specific potential. The purpose of this study is to determine the strengths, weaknesses, opportunities, and threats that Kampung Kauman has, with the result that can study and develop appropriate strategies for developing tourist village with SWOT analysis. A mixed approach, qualitative and quantitative, are both used in this study. To this end, different decisions making tool were used to obtain primary and secondary research data through questionnaires, observation, and documentation. The result of this study showed that the development strategies of Kampung Kauman as a tourist village based on SWOT analysis is stand in quadrant I, this indicates that Kampung Kauman has strength in the form of the social and cultural characteristics that are inherited and still being cultivated until this day. The opportunities that can be utilized for Kampung Kauman development strategies are in the form of the strategically located object location, that in the downtown city, and adjacent to other tourist object, as well as shopping centers.